2015
DOI: 10.1016/j.apenergy.2015.04.096
|View full text |Cite
|
Sign up to set email alerts
|

The performance of small scale multi-generation technologies in achieving cost-optimal and zero-energy office building solutions

Abstract: K. (2015). The performance of small scale multi-generation technologies in achieving cost-optimal and zero-energy office building solutions. Applied Energy, 152,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] Abstract: This study investigates the economic viability of small-scale, multi-generation systems (combined heat and power (CHP), combined cooling, heating, and power (CCHP)), along with conventional heating and cooling systems combining sixteen heating/cooling energy generation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Research with a focus on cost-effective solutions in NZE buildings has been found in [12]. The conclusion of the work conducted in [12] is that ground source heat pumps with free cooling (i.e., ground source heating and cooling, GSHP) is the most optimal solution in regards to economics.…”
Section: Earlier Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Research with a focus on cost-effective solutions in NZE buildings has been found in [12]. The conclusion of the work conducted in [12] is that ground source heat pumps with free cooling (i.e., ground source heating and cooling, GSHP) is the most optimal solution in regards to economics.…”
Section: Earlier Researchmentioning
confidence: 99%
“…The conclusion of the work conducted in [12] is that ground source heat pumps with free cooling (i.e., ground source heating and cooling, GSHP) is the most optimal solution in regards to economics. This is, however, contradicted by another study where a bio-boiler solution is most cost optimal [13].…”
Section: Earlier Researchmentioning
confidence: 99%
“…This decline can best be defined as "performance degradation". It leads to lower energy efficiency and higher life cycle costs than projected, since its effects are generally not being taken into consideration, neither by energy calculation norms nor by conventional simulation models or existing optimization concepts [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this fact, improving the energy performance of buildings is key in reaching the EU target of 20-20-20 (20% CO 2 emissions reduction, 20% increase in energy efficiency and 20% more energy from renewable sources until the year 2020 compared to the levels of 1990) [2]. As a means of achieving this goal, the Energy Performance of Building Directive 2010/31/EU, (EPBD) recast [3] obliges EU member states to evaluate their national requirements on the energy performance of buildings following the so-called "cost optimal methodology".…”
Section: Introductionmentioning
confidence: 99%
“…Single or multiobjective optimization can assist in this endeavor since it allows identifying optimal solutions when several variables are present. Multiobjective optimization enabled Mohamed et al [13] to evaluate system configurations for small-scale multigeneration technologies in zero-energy buildings. The authors identified the optimal solutions in terms of cost and environmental benefits, as well as the effect of including PV panels in the system.…”
Section: Introductionmentioning
confidence: 99%